Sustainability Assessment for Temporary Housing Units - Ezzaroualy, Noura Mohamed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Natural disasters and wars have been happening in recent years because of various factors, such as cultural, political, economic, etc. The conflict has contributed to a considerable rise in refugee numbers. UNHCR suggests that nearly 62 million people had been displaced from their countries and had to flee to areas they believed would be safer. Around 22 million of these people are refugees. The majority of refugees staying in refugee camps are placed in different countries worldwide, which have a population of more than 250000. While most of these refugee camps offer much needed services to the refugees, there are numerous problems in many camps. The critical situation in these camps is that some refugees may continue to live in these places for several years, which may last from five to ten years, and sometimes it may last for decades, these camps gradually turn into small random cities if the camp is not subject to regulation. From this standpoint, this research studies the types of emergency shelters focusing on temporary housing units, which are temporary buildings, to present a proposal to assess these units' sustainability. This thesis aims to propose sustainable temporary housing principles and assessment system to create a new scale to evaluate temporary housing sustainability by using the LEED-H rating system as a base. According to the results, this thesis will evaluate a case in order to test the evaluation system. The evaluation system will be used as a tool for decision making processes.

ÖZ: Son zamanlarda savaşlar kültürel, politik, ekonomik ve bunun gibi çeşitli faktörler yüzünden vuku bulmaktadır. Bu çatışma hatırı sayılır bir miktarda mülteci artışına sebep olmuştur. UNCHR yaklaşık 62 milyon insanın daha güvende olmak için kendi ülkelerini terk edip başka yerlere gittiği öne sürülmüştür. Bu rakamın 22 milyon kadarını da mülteciler oluşturmaktadır. Mülteci kamplarında kalan mültecilerin çoğunluğu dünya üzerinde değişik ülkelere yerleştirilmiştir. Popülasyonu 250000’ı aşan ve şehre benzeyen kamplar bulunmaktadır. Çoğu mülteci kampları gerekli servisleri sağlasa da kamplarda birçok problem baş göstermektedir. Bu kamplarla ilgi kritik nokta bazı mültecilerin bu yerlerde beş ile on yıl süreyle hatta bazen on yıllarca yaşamaya devam edecek olmalarıdır, bu kamplar eğer düzene sokulmazlarsa gitgide rastgele küçük şehirlere dönüşeceklerdir. Bu bakımdan, araştırma afet sonrası geçici konaklama ünitelerine odaklanan ve geçici yapılar olan acil durum barınak çeşitleri önergesi ile bu ünitelerin sürdürebilirliğini değerlendirmeyi ele almaktadır. Bu tez sürdürülebilir geçici konaklama prensipleri ve gelişen ülkelerde bu geçici barınak yerlerinin ölçülmesi üzerine LEED-H değerlendirme sistemini temel alarak yeni bir ölçü tasarısı önermeyi hedeflemektedir. Sonuçlara göre, tez değerlendirme sistemini test etmek için bir örneği değerlendirecektir. Değerlendirme sistemi karar verme sürecinde bir araç olarak kullanılacaktır.
Master of Science in Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2021. Supervisor: Assoc. Prof. Dr. Ercan Hoşkara
Keywords: Architecture Department; Temporary Housing; Immigrants--Housing; Shelters, Refugee Camps, temporary housing, sustainability, sustainability evaluation, LEED-H